(untitled) (Research, Society and Development, 2020)
The objective was to know what health professionals understand about the Clinical Protocol and Therapeutic Guidelines - Thrombolysis in Acute Ischemic Stroke and to develop an informative instrument about it, to be used in the Emergency Care Unit, the study scenario. This is an exploratory, descriptive research, with a qualitative approach, carried out with five nurses and five doctors in an Emergency Care Unit, in the state of Rio Grande do Sul, Brazil. Data were collected during the months of October to November 2019, through semi-structured interviews, and were subjected to content analysis. The results enabled five categories: Clinical protocol as a criterion for thrombolysis; how to use medication and imaging exams; as standardization / organization of care; standardization, cost reduction and clinical improvement of the patient; need for qualification of human, physical and structural resources. In conclusion, the professionals understand that the realization of the protocol would assist in the organization of the service and standardization, as well as in the reduction of expenses and clinical improvement of the patient.